Primary Malignant Melanoma of the Gallbladder: A Case Report and Review of the Literature - Mehmet Fatih Haskaraca; Mustafa Ozsoy; İsmail Özsan; Kamile Kurt (Case Reports in Surgery)
Malignant melanoma is characterized by the ability of diffuse metastases. Since the first report of an isolated malignant melanoma case of the gallbladder, it is already controversial whether isolated cases are metastatic or primary tumors. A 49-year-old woman appealed to the emergency unit because of abdominal pain. Ultrasonography revealed increased thickness of the gallbladder wall and a lesion with surrounding fluid sized 12 mm without acoustic shadow, which arose from the gallbladder wall and was consistent with a polyp. Histopathologic evaluation of the surgical specimen after laparoscopic cholecystectomy revealed malign epithelial tumor consisting of atypical cells with large eosinophilic cytoplasm and dense melanin pigment within the cytoplasm of the tumor cells. As no other focus was identified as a result of the evaluation, the patient was diagnosed with primary malignant melanoma of the gallbladder. In this paper, we aimed to define our treatment modality for a case with isolated malignant melanoma of the gallbladder.